A network analysis of eating disorder symptoms and co-occurring alcohol misuse among heterosexual and sexual minority college women. (July 2021) - Cusack, Claire E.; Christian, Caroline; Drake, Jordan E.; Levinson, Cheri A.
Highlights: Alcohol misuse and eating disorders co-occur driven by unique symptom connections. Frequency of binge drinking may represent a core symptom in this comorbidity. Other core symptoms include both eating disorder and alcohol use symptoms. Drinking in the morning, purging, and guilt connect symptom clusters. Overall symptom relations were similar in heterosexual and sexual minority women. Abstract: Eating disorders and alcohol misuse are common problems among college women. Individually, both have high prevalence rates and are associated with a significant economic burden. Yet eating disorders and alcohol misuse also frequently present simultaneously, which may increase symptom severity and related impairment. These associations are especially important to test in sexual minority populations, as symptoms may present differently, and the prevalence and personal cost of these disorders may be even higher for this group. The present study ( N = 1072 undergraduate college women) used network analysis to identify pathways, central symptoms, and bridge symptoms across alcohol misuse and eating disorder symptoms. A network comparison test was used to determine if the network structure differed between heterosexual women ( n = 923) and sexual minority women ( n = 149). For the overall network, cognitive restraint, excessive exercise, and frequency of binge drinking, were the most central symptoms. Bridge symptoms included drinking in the morning, purging, alcohol-related guilt, and muscle building. Heterosexual and sexual minority women did not differ significantly in network structure or global strength. Regardless of sexual orientation, prevention efforts for eating disorders and alcohol misuse among college women should target central and bridge symptoms.